Pesticides and human diabetes: a pilot project to explore a possible link. (April 2015) - Swaminathan, K; Thangavel, G
Abstract: An increasing number of studies show an association between environmental pollutants – especially organophosphorous pesticides – and the development of insulin resistance and hyperglycaemia. Our aim was to explore this hypothesis in farming communities around the city of Madurai, India. Local Ethics Committee approval was obtained. In all, 260 participants more than 18 years of age from farming villages around Madurai were evaluated based on three categories of pesticide exposure. The crude odds ratio for farmers mixing and spraying pesticides to have diabetes compared to the minimal exposure category was 2.07 (95% CI 1.01–4.24). After adjusting for sex and BMI, the odds ratio was 2.302 (95% CI 1.082–4.896). There seems to be a moderate association between pesticide exposure and diabetes. A good study design and good control of confounding factors will testify to this association. Copyright © 2015 John Wiley & Sons.